The impact of the management by values (MBV) on the competitiveness of Saudi Arabia Hospitals Al-Qassim Region - Althair, Gamaleldeen Osman; Mohieldin, Mohieldin Ali (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aimed to examine the impact of management by values (MBV) on the competitive advantage of hospitals in the Kingdom of Saudi Arabia, with a specific focus on the Qassim region. To achieve this goal, the study adopted a quantitative methodology by distributing questionnaires to a sample of hospital employees and analyzing the data using statistical techniques. The findings revealed that adopting MBV significantly enhances hospital competitiveness by strengthening human, informational, and technological capabilities. Furthermore, the study showed that organizational values play a vital role in increasing institutional loyalty and employee satisfaction, which positively affects the quality of healthcare services provided. Additionally, hospitals that implement value-based management were found to be more capable of addressing organizational challenges and adapting to environmental changes. The study recommends promoting a culture of value-based management in hospitals by training administrative leaders on its application and encouraging employees to actively participate in developing organizational values. It also highlights the need to improve information systems and technology and adopt advanced human resource policies that foster a stable work environment, thereby enhancing the competitiveness of Saudi hospitals in the healthcare sector.
Keywords: Management by Values; Competitiveness; Organizational Values; Employee Satisfaction; Healthcare Service Quality